Diabetes and Peripheral Vascular Disease Diagnosis and Management - Shrikhande, Gautam V.; McKinsey, James F. (Contemporary Diabetes,, 2012)
In Diabetes and Peripheral Vascular Disease, a panel of distinguished leaders in the field of medicine, podiatry, and vascular and endovascular therapy assimilate the latest literature on these issues and others for an in-depth review of the management of peripheral vascular disease. Providing an overview of the management of diabetes and diabetic foot changes as well as providing a view of cutting-edge and emerging topics in optimization of arterial status, this important title addresses pathophysiology, anatomy, diagnosis and management of diabetic peripheral vascular disease, emphasizing a multi-disciplinary approach. The first chapter of the book provides an overview of this complex disease process and discusses the teamwork required for optimal management. The chapters continue with the basic pathophysiology of diabetic atherosclerosis and a contemporary review of the management of diabetes. The genesis of diabetic foot ulceration and prevention and management strategies is covered, as is the effects of neuropathy and microvascular changes in the diabetic foot. In addition, Diabetes and Peripheral Vascular Disease covers the microbiology of diabetic foot infections, the role of endovascular interventions and vascular surgery as well as the management of the complications of these procedures, the process of amputation for those patients who have progressed beyond a limb salvage situation, and the effects of diabetes on the cerebrovascular system as well as its implications in patients with aortoiliac disease. An invaluable addition to the literature on diabetes and peripheral vascular disease, the book will be of great interest internists, family practitioners, surgeons, podiatrists, wound care specialists, and vascular specialists. Students, residents, and fellows in surgical and medical specialties should also find this book of significant value and interest.